Combining SARS-CoV-2 Proofreading Exonuclease and RNA-Dependent RNA Polymerase Inhibitors as a Strategy to Combat COVID-19: A High-Throughput in silico Screening - Khater, Shradha; Kumar, Pawan; Dasgupta, Nandini; Das, Gautam; Ray, Shashikant; Prakash, Amresh (Frontiers in Microbiology, 2021)
SARS-CoV-2 has infected millions of people worldwide. Currently, many clinical trials in search of effective COVID-19 drugs are underway. Viral RNA-dependent RNA polymerase (RdRp) remains the target of choice for prophylactic or curative treatment of COVID-19. Nucleoside analogs are the most promising RdRp inhibitors and have shown effectiveness in vitro as well as in clinical settings. One limitation of such RdRp inhibitors is the removal of incorporated nucleoside analogs by SARS-CoV-2 exonuclease (ExoN). Thus, ExoN proofreading activity accomplishes resistance to many of the RdRp inhibitors. We hypothesize that in the absence of highly efficient antivirals to treat COVID-19, combinatorial drug therapy with RdRp and ExoN inhibitors will be a promising strategy to combat the disease. To repurpose drugs for COVID-19 treatment, 10,397 conformers of 2,240 approved drugs were screened against the ExoN domain of nsp14 using AutoDock VINA. The molecular docking approach and detailed study of interactions helped us to identify Dexamethasone metasulfobenzoate, Conivaptan, Hesperidin and Glycyrrhizic acid as potential inhibitors of ExoN activity. The results were further confirmed using Molecular Dynamics simulations and MM-GBSA calculations. Further, the binding free energy of Conivaptan and Hesperidin, estimated using MM-GBSA, was -85.86±0.68 and 119.07±0.69 kcal/mol respectively. Based on docking, molecular dynamics simulations and known antiviral activities, Conivaptan and Hesperidin were identified as potential SARS-CoV-2 ExoN inhibitors. We recommend further investigation of this combinational therapy using RdRp inhibitors with a repurposed ExoN inhibitor as a potential COVID-19 treatment.